Transformasi Kurikulum Merdeka Dalam Perspektif John Dewey - Ubaidillah, Sofwan Roif; Laili, Wahdania Rohmatul; Wahono, Suparwoto Sapto; Machfudi, Moch. Imam (IJIT: Indonesian Journal of Islamic Teaching, 2024)
Education plays an important role in developing human character and potential. The Merdeka Curriculum in Indonesia is present as a solution to the need for a more relevant and adaptive education system in an era of rapid change. This curriculum prioritizes experience-based learning to develop students' competencies independently, in line with John Dewey's pragmatism educational philosophy, which emphasizes the relevance of learning to real life and practical skills. This research uses descriptive qualitative methods with literature study to analyze relevant literature. The aim of the research is to examine the implementation of the Independent Curriculum through the perspective of Dewey's pragmatism, with a focus on experience-based learning and the development of 21st century skills. Despite challenges such as limited resources and teacher readiness, the Merdeka Curriculum has the potential to improve the quality of education by creating a more flexible learning environment. This research aims to provide insight for policy makers and educational practitioners in formulating more effective curriculum implementation strategies.